Análise histopatológica e morfométrica das brânquias de peixes da espécie Poecilia reticulata expostos a azitromicina - Tagliamento, Manuela Agulló [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The gills are essential organs in the functioning of aquatic organisms, playing a fundamental role in various functions such as gas exchange, osmoregulation, ionic balance, and excretion. As they are in direct contact with the external environment, they are susceptible to changes in the environment, such as the presence of contaminants, which makes them excellent biomarkers of environmental quality, as they greatly reflect the acute and chronic effects caused by contamination. Among the various contaminants found in aquatic environments, azithromycin, an anti-inflammatory antibiotic with immunomodulatory activity, has been used and disposed of exponentially since the Covid-19 pandemic, making it an environmental problem mainly due to the lack of information on its effects on aquatic organisms and, consequently, the lack of specific regulations. Therefore, the objective of the work was to understand the histopathological and morphometric changes caused by exposure to different concentrations of azithromycin. Among the results, demonstrative responses were seen, especially at concentrations of 16 ug/L and depurantion, which raises great concern, given that, regardless of whether the transport of azithromycin in the environment decreases or completely ceases, its residual, even if small, will continue implicating in various structural and functional changes to non-target organisms that encounter it, which ends up interfering with the entire chain and ecology of ecosystems.

As brânquias são órgãos essenciais na funcionalidade de organismos aquáticos, desempenhando papel fundamental em diversas funções, como trocas gasosas, osmorregulação, equilíbrio iônico e excreção. Por estarem em contato direto com o ambiente externo, ficam suscetíveis a alterações no meio, como por exemplo, a presença de contaminantes, o que as tornam excelentes biomarcadores de qualidade ambiental, dado que refletem grandemente os efeitos agudos e crônicos causados pela contaminação. Dentre os diversos contaminantes encontrados nos ambientes aquáticos, a azitromicina, um antibiótico anti-inflamatório com atividade imunomoduladora, têm seu uso e descarte crescente de maneira exponencial desde a pandemia do Covid-19, o que a torna um problema ambiental principalmente devido à ausência de informações de seus efeitos aos organismos aquáticos e, consequentemente, ausência de regulamentações específicas. Assim, o objetivo do trabalho foi compreender as alterações histopatológicas e morfométricas causadas pela exposição a diferentes concentrações de azitromicina. Dentre os resultados, observou-se maiores respostas especialmente nas concentrações 16 ug/L e depuração, o que gera grande preocupação, dado que, independente se o aporte da azitromicina no ambiente diminua ou cesse completamente, sua presença residual, mesmo que pequena, continuará implicando em diversas alterações estruturais e funcionais aos organismos não-alvo que a encontram, o que acaba interferindo em toda a cadeia e ecologia dos ecossistemas.
Histopathological and morphometric analysis of the gills of Poecilia reticulata fish exposed to azithromycin
Keywords: Contaminantes emergentes na água; Azitromicina; Morfometria; Histopatologia